PENENTUAN KECEPATAN DAN PERCEPATAN MEKANISME ENGKOL PELUNCUR PADA KOMPONEN MESIN - Naharuddin, Naharuddin (Jurnal MEKANIKAL, 2012)
The purpose of this research is to analyze the crank shaft mechanism theoretically with trigonometry and complex number methods. Equation of velocity and acceleration of these methods are taken the same and the difference of influnced variables. The same variables are angle position, angle velocity, and beam length 2 and linking beam length 3. The differences is for complex number analysis influenced by angle position, angle velocity and beam angle acceleration 3. Based on used variable for these methods, trigonometry analysis can be applied if crank shaft angle velocity is a constant. Calculation of velocity and acceleration are based on beam angle 2 change from 0o - 360o with angle range 15o counter clock watch (CCW), crank angle velocity 188.4 rad/s, length of beam 2 (0.05 m, 0.075 m. 0.10 m) and length of beam 3 (0.3 m). The result of trigonometry and complex number calculation for variation of beam lenght 2 is taken the difference of velocity and acceleration on piston. The difference percentages of velocity are 8.25%, 12.76%, and 17.78 % respectively and of acceleration are 0.50%, 2.34%, and 19.91 % respectively.